Intermittent Starvation Promotes Maturation of Human Embryonic Stem Cell-Derived Cardiomyocytes - Yang, Jingsi; Ding, Nan; Zhao, Dandan; Yu, Yunsheng; Shao, Chunlai; Ni, Xuan; Zhao, Zhen-Ao; Li, Zhen; Chen, Jianquan; Ying, Zheng; Yu, Miao; Lei, Wei; et al. (Frontiers in Cell and Developmental Biology, 2021)
Human pluripotent stem cell-derived cardiomyocytes (hPSC-CMs) represent an infinite cell source for cardiovascular disease modeling, drug screening and cell therapy. Despite extensive efforts, current approaches have failed to generate hPSC-CMs with fully adult-like phenotypes in vitro, and the immature properties of hPSC-CMs in structure, metabolism and electrophysiology have long been impeding their basic and clinical applications. The prenatal-to-postnatal transition, accompanied by severe nutrient starvation and autophagosome formation in the heart, is believed to be a critical window for cardiomyocyte maturation. In this study, we developed a new strategy, mimicking the in vivo starvation event by Earle’s balanced salt solution (EBSS) treatment, to promote hPSC-CM maturation in vitro. We found that EBSS-induced starvation obviously activated autophagy and mitophagy in human embryonic stem cell-derived cardiomyocytes (hESC-CMs). Intermittent starvation, via 2-hour EBSS treatment per day for 10 days, significantly promoted the structural, metabolic and electrophysiological maturation of hESC-CMs. Structurally, the EBSS-treated hESC-CMs showed a larger cell size, more organized contractile cytoskeleton, higher ratio of multinucleation, and significantly increased expression of structure makers of cardiomyocytes. Metabolically, EBSS-induced starvation increased the mitochondrial content in hESC-CMs and promoted their capability of oxidative phosphorylation. Functionally, EBSS-induced starvation strengthened electrophysiological maturation, as indicated by the increased action potential duration at 90% and 50% repolarization and the calcium handling capacity. In conclusion, our data indicate that EBSS intermittent starvation is a simple and efficient approach to promote hESC-CM maturation in structure, metabolism and electrophysiology at an affordable time and cost.